Qu’est-ce que la critique dans la philosophie critique de la race ? - Magali Bessone (Astérion)
The article takes the notion of critique seriously in order to evaluate to what extent, according to what characterisations, under what conditions, and with what limits critical philosophy of race (CPR), which refers to critical race theory specifically in the philosophical field, constitutes critical knowledge. The first section presents the way in which CPR defines itself in contrast to non-critical philosophy of race, in terms of philosophical canon, methods, and assessment of the central concepts of the field: this allows us to identify, negatively, the function attributed to critique, methodologically and theoretically. The second section identifies three possible meanings for critical race thinking according to the three major theoretical influences in the field: Foucauldian genealogy, critical theory, and critical phenomenology. Finally, a concluding section focuses on how the three critical schools defend various objectives in their relation to truth, to the positioning of the subject of knowledge, and to transformative action.